Paracoccus luteus sp. nov., isolated from the intestine of grass carp. Issue 1 (3rd February 2020) - Ming, Hong; Cheng, Li-Jiao; Ding, Chen-Long; Niu, Ming-Ming; Zhao, Zhuo-Li; Ji, Wei-Li; Zhang, Ling-Yu; Zhang, Yan-min; Meng, Xiao-Lin; Nie, Guo-Xing
Abstract : A novel Gram-negative bacterium, designated CFH 10530 T, was isolated from the intestine of grass carp. The sample was collected from the aquaculture training base at the College of Fisheries, Henan Normal University, Xinxiang, PR China. Cells of strain CFH 10530 T were coccoid, ovoid or short-rod-shaped, aerobic, non-spore-forming and non-motile. 16S rRNA gene sequence analysis demonstrated that strain CFH 10530 T was closely related to Paracoccus endophyticus SYSUP0003 T (97.7 % sequence similarity), Paracoccus halophilus HN-182 T (96.5 %) and Paracoccus panacisoli DCY94 T (96.1 %). The strain grew optimally at 25–28 °C, at pH 7.0 and with 0–2 % (w/v) NaCl. Cells were positive for catalase and oxidase, nitrate was reduced and H2 S was not produced. The isoprenoid quinone was Q-10. Major cellular fatty acids were summed feature 8, C18 : 0 and C18 : 0 3-OH. The major polar lipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylcholine, one unidentified aminolipid and five unidentified polar lipids. The genome size was 3 331 229 bp with a G+C content of 69.6 mol%. The average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) values between CFH 10530 T and the other species of the genus Paracoccus were found to be below the recommended levels for species delineation (ANIm <85, ANIb <80 and dDDH <24 %). Based on its physiological properties, chemotaxonomic characteristics and low ANI and dDDH results, strain CFH 10530 T is considered to represent a novel species for which the name Paracoccus luteus sp. nov., is proposed. The type strain is CFH 10530 T (=KCTC 62919 T =CGMCC 1.16597 T ).